Challenges and Opportunities of STEAM-based Learning in Pancasila Education: A Case Study at SDN 1 Bunulrejo Malang - Helga Salsabila; Sabrina Azzahro; Sigit Priatmoko; Wiku Aji Sugiri; Rizki Amelia (Prosiding Seminar Nasional Pendidikan FKIP Universitas Lampung, 2025)
Pancasila Education is an important subject in elementary school. Some previous research shows that Pancasila Education learning in elementary schools is less attractive to students. One of the innovative approaches that is relevant to be used in learning Pancasila Education is STEAM. This study aims to explore the planning, implementation, evaluation, and factors influencing the implementation of STEAM-based Pancasila Education learning. This case study was conducted at SDN 1 Bunulrejo, Malang—one of the primary schools that prioritizes technology-based learning and STEAM implementation. Data were collected using semi-structured interviews, non-participant observation, and document analysis. Data analysis used thematic analysis. The findings show that integrating STEAM in Pancasila Education contributes to holistic learner character building and makes learning more effective and efficient.